Fifth formers of st clare's - Blyton,Enid (London: Egmont UK Ltd, 2013)
Being in the fifth form has lots of changes like having their own study instead of common room, Mirabel as sports captain and new girls. They face challenges related to stealing and it ends with twins as Head girls for next term.